Uji Aktivitas Antibakteri Daun Singkong (Manihot esculenta) Pada Bakteri Staphylococcus aureus dan Eschrichia coli - Prasasti, Azmi; Kustriyani, Anung; Udianto, Abi Mas; Permatasari, Velisia Dini; Oktalia, Putri; Nursiyatin, Nursiyatin (Bioeksperimen: Jurnal Penelitian Biologi, 2022)
Staphylococcus aureus and Escherichia coli are bacteria that cause infections and they are often found in the community. Infections caused by these bacteria are usually treated with antibiotics. However, excessive and uncontrolled use of antibiotics can lead to antibiotic resistance or immunity. This can result the infection will be more difficult to treat because of the bacteria's resistance to the antibiotic. Thus,  the treatment to minimize side effects of antibiotics resistance is needed. One of the traetment is using the herbal ingredients. Cassava leaves are plants with various properties, one of which is antibacterial. Therefore, this study aimed to determine the content of secondary metabolites and to test the antibacterial activity of cassava leaf extract on S. aureus and E. coli bacteria. The extraction method uses maceration. Antibacterial test using paper disc method test. Variations in the concentration of cassava leaf extract were 50,000 ppm, 100,000 ppm, and 150,000 ppm. The results showed that cassava leaf extract contained alkaloids, flavonoids, tannins, saponins and was able to inhibit the growth of S. aureus and E. coli bacteria. In S. aureus, the concentration of 150,000 ppm produced the highest inhibition zone of 11.1 mm and the concentration of 50,000 ppm produced the lowest inhibition zone of 8.6 mm. In E. coli a concentration of 150,000 ppm resulted in the highest inhibition zone of 5.2 mm and the lowest concentration of 3.5 mm. The response of cassava leaf extract was classified as a moderate response in inhibiting the growth of S. aureus bacteria. While producing a weak response in inhibiting the growth of E. coli bacteria. Statistical test for the inhibition zone of S. aureus showed normality of 0.500 and homogeneous 0.286, while for the inhibition zone of E.coli showed normal 0.96 and homogeneous 0.281.